Knowledge management in tourism industry. - Ng, Wei Lun. (2009)
This study seeks to explore into Organization Learning, Knowledge Management (KM) and Knowledge Sharing (KS) processes in the tourism industry. Prior researches have indicated that human behavior is a triadic reciprocality between personal factors, behavior, and environment [Wood, 1989]; [Bandura A., 1986]; [Compeau & Higgins, 1995]; [Glanz, 2002]. Therefore, this study seeks to understand how two hotels in the tourism industry, Starwood Asia Pacific Hotels & Resorts and Carlson Hotels Worldwide, implement their organization learning, KM, and KS processes which could be affected by the three factors mentioned and what impact does these factors have on the processes.